2020
DOI: 10.5603/ep.a2020.0049
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thyroid hormone status on selected antioxidant parameters in patients with Graves’ disease and active thyroid-associated orbitopathy

Abstract: Introduction: Oxidative stress has been implicated in the pathogenesis of thyroid-associated orbitopathy (TAO) in patients with Graves' disease (GD). This study assessed the effect of thyroid hormone abnormalities on selected antioxidant parameters in patients with active TAO. Material and methods:The study group consisted of 56 patients with GD and active TAO treated with antithyroid medication. Depending on the thyroid hormone level, they were subdivided into two groups: Group 1 -hyperthyroid patients (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…It has been reported that the thyroid hormone, like autoimmune in ammation, is a signi cant contributor to oxidative stress in patients with TAO, which manifests as upregulated lipid peroxidation and antioxidant system activation [21,22]. It is found that euthyroid state restoration leads to a relative reduction in activity and levels of most antioxidant parameters [23,24]. Thus, the autoimmune in ammation of the orbital tissue and thyroid hormone status seem to be mutually independent modi ers of TAO activity which may explain the fact that CAS score is related to hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the thyroid hormone, like autoimmune in ammation, is a signi cant contributor to oxidative stress in patients with TAO, which manifests as upregulated lipid peroxidation and antioxidant system activation [21,22]. It is found that euthyroid state restoration leads to a relative reduction in activity and levels of most antioxidant parameters [23,24]. Thus, the autoimmune in ammation of the orbital tissue and thyroid hormone status seem to be mutually independent modi ers of TAO activity which may explain the fact that CAS score is related to hormone levels.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 20 papers met the inclusion criteria and were considered in this review [ Figure 1 ]. There were four human studies 20 21 22 23 and sixteen in vitro studies 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 from 1993 to 2021 [ Table 2 ]. Fifteen studies were from Taiwan (2), Canada (1), Greece (1), Brazil (2), Poland (1), the USA (1), Japan (1), Italy (5), South Korea (3), Germany (1), China (1), and one was supervised by the international multicentral European Group on Graves' Orbitopathy (EUGOGO) association.…”
Section: R Esultsmentioning
confidence: 99%
“…Bednarek et al reported elevated blood levels of H 2 O 2 , lipid hydroperoxide (ROOH), TBARS, and ceruloplasmin as well as increased SOD and CAT activities but reduced GPx and glutathione reductase activities in patients with GD [ 24 , 33 ]. These parameters were normalized after achieving euthyroidism in the study population except those with GO, indicating that the contribution of orbital inflammation to oxidative stress was independent of thyroid hormones [ 33 , 51 ].…”
Section: In Vivo Evidence Of Oxidative Stress In Graves’ Ophthalmopathymentioning
confidence: 99%
“…In addition, 6.25 μM H 2 O 2 upregulated TGF-β1, IL-1β, and O 2 •− in orbital fibroblasts from patients with GO [ 28 ]. It is believed that IL-1β induces inflammatory cytokines and that TGF-β1 promotes tissue remodeling and fibrosis through myofibroblast transdifferentiation in GO orbital fibroblasts [ 51 , 53 ]. These processes are critical in the pathogenesis of GO.…”
Section: In Vitro Evidence On Oxidative Stress In Graves’ Ophthalmopathymentioning
confidence: 99%